Electrochemical Quantification of the Antioxidant Capacity of Medicinal Plants Using Biosensors - Rodríguez-Sevilla, Erika (MDPI, 2014)
The working area of a screen-printed electrode, SPE, was modified with the enzyme tyrosinase (Tyr) using different immobilization methods, namely entrapment with water-soluble polyvinyl alcohol (PVA), cross-linking using glutaraldehyde (GA), and cross-linking using GA and human serum albumin (HSA); the resulting electrodes were termed SPE/Tyr/PVA, SPE/Tyr/GA and SPE/Tyr/HSA/GA, respectively. These biosensors were characterized by means of amperometry and EIS techniques. From amperometric evaluations, the apparent Michaelis-Menten constant, K(m)′, of each biosensor was evaluated while the respective charge transfer resistance, Rct, was assessed from impedance measurements. It was found that the SPE/Tyr/GA had the smallest K(m)′ (57 ± 7) μM and Rct values. This electrode also displayed both the lowest detection and quantification limits for catechol quantification. Using the SPE/Tyr/GA, the Trolox Equivalent Antioxidant Capacity (TEAC) was determined from infusions prepared with “mirto” (Salvia microphylla), “hHierba dulce” (Lippia dulcis) and “salve real” (Lippia alba), medicinal plants commonly used in Mexico.